Spregledani podnaslov - Fock, Ignac (Vestnik za tuje jezike, 2012)
The present article is an intertextual study of Flaubert's novel Madame Bovary and his fragmentary, posthumously published work Dictionary of accepted ideas. By listing examples of thematic parallelisms as well as those in formulation, the author proves the presence of certain sociological, historical and literary patterns which are, almost theoretically, concretized as accepted ideas in the Dictionary whereas in a novelistic form, they shape a kind of "social scenery", paraphrased also by the subtitle of Madame Bovary: Patterns of provincial life. He consequently warns that Madame Bovary is not (merely) a novel about Emma Bovary whose story is, furthermore, given a meaning, if not even justified, only by the mentioned patterns of provincial life. In Flaubert's work, conceptualisation and literarisation of the "universally acknowledged" are simultaneous and no temporal priority can thus be discussed. However, in Madame Bovary it is precisely under the form of social scenery that is reproduced the concise satire of the Dictionary, the latter being therefore perceived by the author as a cross section and a synthesis of the novelist's entire work as well as a complementary reading to this particular novel.
Keywords: Flaubert, Gustave, 1821-1880; Gospa Bovary; Madame Bovary; Slovar splošno priznanih resnic; Dictionnaire des idées reçues; francoska književnost; French literature; intertekstualnost; Intertextuality; medbesedilnost